2010
DOI: 10.1007/s00340-010-4017-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dual-wavelengths fiber ring laser utilizing a phase-only sampled fiber Bragg grating with multiple phase-shifts inserted

Abstract: A simple technique to multiply the lasing wavelength in a semiconductor optical amplifier (SOA)-based fiber ring laser is proposed and demonstrated, which is based on the utilization of a multiple phase-shifts sampled fiber Bragg grating(FBG). Tunability for the wavelength spacing within each dual-wavelengths has also been demonstrated by changing the positions of phase shifts. Moreover, more than 20 dual-wavelengths fiber lasers with a 3-dB linewidth of 0.017 nm and signal-to-noise ratio (SNR) of about 45 dB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Interestingly, Ning, et al have demonstrated a multiple dual-wavelength fiber laser incorporating a polarization-maintaining Fabry-Perot filter [37], and used it to realize multiple-channel microwave photonic filters by combining the wavelength-divisionmultiplexing technique and the frequency beating technique, which is equivalent to a series of dualwavelength fiber lasers for microwave generation or filtering [38]. Recently, Chen, et al further reported a spacing-tunable multiple dual-wavelength fiber laser by utilizing a multiple phase shifts phase-only sampled fiber Bragg grating [39]. However, for both of these cases, fabrication of the abnormal comb filters is complex and at high costs, which has some constraints in the flexibility of laser output.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Ning, et al have demonstrated a multiple dual-wavelength fiber laser incorporating a polarization-maintaining Fabry-Perot filter [37], and used it to realize multiple-channel microwave photonic filters by combining the wavelength-divisionmultiplexing technique and the frequency beating technique, which is equivalent to a series of dualwavelength fiber lasers for microwave generation or filtering [38]. Recently, Chen, et al further reported a spacing-tunable multiple dual-wavelength fiber laser by utilizing a multiple phase shifts phase-only sampled fiber Bragg grating [39]. However, for both of these cases, fabrication of the abnormal comb filters is complex and at high costs, which has some constraints in the flexibility of laser output.…”
Section: Introductionmentioning
confidence: 99%